2022
DOI: 10.1002/rse2.297
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning algorithm outperforms experienced human observer at detection of blue whale D‐calls: a double‐observer analysis

Abstract: An automated algorithm for passive acoustic detection of blue whale D‐calls was developed based on established deep learning methods for image recognition via the DenseNet architecture. The detector was trained on annotated acoustic recordings from the Antarctic, and performance of the detector was assessed by calculating precision and recall using a separate independent dataset also from the Antarctic. Detections from both the human analyst and automated detector were then inspected by an independent judge to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…In fact, WST can assist us to extract significant features for LSTM in those situations when it is not possible to learn efficient features with the available training data in case of data scarcity. This makes our proposed scheme for use, such as few-shot learning [ 29 ] for identification of endangered whale calls unlike the existing recent deep-learning-based methods [ 2 , 3 , 7 , 8 ] that require large datasets for learning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, WST can assist us to extract significant features for LSTM in those situations when it is not possible to learn efficient features with the available training data in case of data scarcity. This makes our proposed scheme for use, such as few-shot learning [ 29 ] for identification of endangered whale calls unlike the existing recent deep-learning-based methods [ 2 , 3 , 7 , 8 ] that require large datasets for learning.…”
Section: Discussionmentioning
confidence: 99%
“…Blue whales are known to produce downswept FM (frequency-modulated) calls that are often referred as D-calls. Both male and female blue whales have been found to produce such calls [ 3 ]. On the contrary, it is observed that only males produce song, and with that, these calls are associated with the breeding season.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, signals in passive acoustic data are classified by human analysts who generally are supported by software that provides visualisation, audition, and analysis of the recordings. Signal analysis by humans usually is treated as the standard against which automated detectors should be compared (although see Miller et al ., 2023), but can be slow and incur labour costs and delay. Differences in expertise among analysts, a given analyst's attention span on a particular day, and other inconsistencies lead to variability within and among human analysts (Širović, 2016; Leroy et al ., 2018), creating non‐systematic biases.…”
Section: Passive Acoustic Sampling and Analysis In An Ecological Contextmentioning
confidence: 99%